A new Paralimnini leafhopper genus (Hemiptera: Cicadellidae: Deltocephalinae) from China - Xing, Ji–Chun; Dai, Ren–Huai; Li, Zi–Zhong (Zootaxa, 2011)
With over 6500 described species placed in nearly 800 genera the leafhopper subfamily Deltocephalinae is currently the largest subfamily of Cicadellidae (Oman et al.,1990; Zahniser & Dietrich, 2008; Zahniser & Dietrich, 2010). The deltocephaline tribe Paralimnini Distant is distributed worldwide and currently contains about 132 genera and 550 species. Webb and Heller (1990) provided a checklist of Oriental Paralimnini with 11 genera and 23 species, among them, 2 genera and 2 species recorded from China. Zhang (1990) only recorded 1 genus and 1 species in this tribe from China. More recently, a total of 26 genera (12 genera in the Oriental Region) and 62 species of the Paralimnini have been reported to occur in China (Xing et al., 2009, 2010, 2011; Xing & Li, 2011; Li et al., 2011; Zhang et al., 2009). Most members of the tribe are closely associated with grass dominated habitats. With the exception of some species of Paralaevicephalus Ishihara (Xing et al. 2009) members of the Paralimnini can be recognized by having a connective that is widest at or near the base of the anterior arms and articulated with the aedeagus. During a study of the Chinese Deltocephalinae we discovered a new Oriental paralimnine genus and species that are described below. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).